Host Galaxies for Four Nearby CHIME/FRB Sources and the Local Universe FRB Host Galaxy Population - Mohit Bhardwaj; Daniele Michilli; Aida Yu. Kirichenko; Obinna Modilim; Kaitlyn Shin; Victoria M. Kaspi; Bridget C. Andersen; Tomas Cassanelli; Charanjot Brar; Shami Chatterjee; Amanda M. Cook; Fengqiu Adam Dong; et al. (The Astrophysical Journal Letters, 2024)
We present the host galaxies of four apparently nonrepeating fast radio bursts (FRBs), FRB 20181223C, FRB 20190418A, FRB 20191220A, and FRB 20190425A, reported in the first Canadian Hydrogen Intensity Mapping Experiment (CHIME/FRB) catalog. Our selection of these FRBs is based on a planned hypothesis testing framework where we search all CHIME/FRB Catalog-1 events that have low extragalactic dispersion measure (<100 pc cm ^−3 ), with high Galactic latitude (∣ b ∣ > 10°) and saved baseband data. We associate the selected FRBs with galaxies with moderate to high star formation rates located at redshifts between 0.027 and 0.071. We also search for possible multimessenger counterparts, including persistent compact radio and gravitational-wave sources, and find none. Utilizing the four FRB hosts from this study, along with the hosts of 14 published local Universe FRBs ( z < 0.1) with robust host association, we conduct an FRB host demographics analysis. We find all 18 local Universe FRB hosts in our sample to be spirals (or late-type galaxies), including the host of FRB 20220509G, which was previously reported to be elliptical. Using this observation, we scrutinize proposed FRB source formation channels and argue that core-collapse supernovae are likely the dominant channel to form FRB sources. Moreover, we infer no significant difference in the host properties of repeating and apparently nonrepeating FRBs in our local Universe FRB host sample. Finally, we find the burst rates of these four apparently nonrepeating FRBs to be consistent with those of the sample of localized repeating FRBs observed by CHIME/FRB. Therefore, we encourage further monitoring of these FRBs with more sensitive radio telescopes.